2014
DOI: 10.4111/kju.2014.55.7.482
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Uncommon Computed Tomography Findings and Clinical Aspects in Patients With Acute Pyelonephritis

Abstract: PurposeComputed tomography (CT) has become popular in the diagnosis of acute pyelonephritis (APN) and its related complications in adults. The aim of this study was to investigate the relationship between uncommon CT findings and clinical and laboratory data in patients with APN.Materials and MethodsFrom July 2009 to July 2012, CT findings and clinical data were collected from 125 female patients with APN. The six uncommon CT findings (excluding a wedge-shaped area of hypoperfusion in the renal parenchyma) stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Renal parenchymal inflammation causes perirenal tissue changes that are recognized as perirenal fat stranding and thickening of perirenal fasciae. Kim et al investigated the relationship between "uncommon CT findings" and clinical aspects in APN; however, the most common CT finding was perirenal fat infiltration (55% of cases) [7]. Our results and previous studies suggest that the perirenal tissue change detected by CT scanning is a common pathogenesis of APN.…”
Section: Discussionsupporting
confidence: 54%
“…Renal parenchymal inflammation causes perirenal tissue changes that are recognized as perirenal fat stranding and thickening of perirenal fasciae. Kim et al investigated the relationship between "uncommon CT findings" and clinical aspects in APN; however, the most common CT finding was perirenal fat infiltration (55% of cases) [7]. Our results and previous studies suggest that the perirenal tissue change detected by CT scanning is a common pathogenesis of APN.…”
Section: Discussionsupporting
confidence: 54%
“…Kim et al showed that CT image grading could be used to predict the severity and course of disease [32]. The higher the CT grades were, the worse the clinical symptoms and the prognosis were [32]. By CT grading, we evaluated the degree of kidney infection and our results may better guide the treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, results of the study showed that the higher the CT grade was, the greater the risk of SIRS in patients with upper urinary tract calculi were, which provides clinical guidance for early clinical diagnosis and treatment of SIRS. Kim et al showed that CT image grading could be used to predict the severity and course of disease [32]. The higher the CT grades were, the worse the clinical symptoms and the prognosis were [32].…”
Section: Discussionmentioning
confidence: 99%
“… 22 Perirenal fat infiltration is observed when the inflammation of the renal parenchyma spreads beyond the renal capsule into the perirenal fat. 7 The stranding likely represents fluid that collects within the bridging septa of the perinephric fat as a result of increased lymphatic pressure. Fluid collections may become asymmetric in the presence of unilateral obstruction or pyelonephritis.…”
Section: Discussionmentioning
confidence: 99%
“… 1 2 4 5 6 ECT shows both the intrarenal and extrarenal areas as precise images and provides comprehensive anatomical information. 7 It also enables the detection of complications such as renal or perinephric abscess. 8 However, the administration of iodinated contrast agents used during ECT increases the risk of contrast-induced acute kidney injury (CIAKI).…”
Section: Introductionmentioning
confidence: 99%